Analisis Bibliometrik Data Publikasi Penanganan Covid-19 ii Indonesia Menggunakan Software Vosviewer dan Tableau - Tupan Tupan; Nur Rizzal Rosiyan (Perpustakaan Nasional RI, 2022)
Bibliometric analysis of publicity data on the handling of Covid-19 in Indonesia was carried out using Tableau and Vosviewer software. The research was conducted by using the literature search method using Google Scholar. The search was carried out from March 2020 to September 2020 using the keywords Covid-19 and Indonesia. The search results are then grouped based on author name, title and publication source. The results of grouping publications for Covid-19 handlers using Microsof Exel are grouped based on handling criteria. For publication sources analyzed using Software Tableau. Meanwhile, writer collaboration and keyword mapping were analyzed using the VosViewer software. The results of the analysis based on the criteria for handling Covid-19 show that most publications are in the form of treatment / prevention then followed by the impact / effect. Collaboration analysis using VosViewer software shows that Ian Huang is the most collaborative writer with 20 publications, followed by Raymond Pranata with 15 publications. The most publications on handling Covid-19 were published in Medica Hospitalia with 29 articles, followed by SALAM: Syar'i Social and Cultural Journal with 18 articles. Mapping results using VosViewer show that the handling of Covid-19 is divided into 4 clusters. Based on the visualization map, it is known that the most widely carried out research publications on Covid-19 are prevention / control in the context of accelerating the handling of the Covid pandemic, then followed by government policies in dealing with Covid-19 and economic policies during the Covid-19 pandemic.